GEREJA DAN KETAHANAN PANGAN: REFLEKSI TEOLOGIS DARI TRADISI AGRARIS UMAT ALLAH DALAM PENGELOLAAN TANAH - Mulyo Kadarmanto; Ike Albert Hepi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
This writing aims to investigate the life of Israel as an agrarian society in the management and utilization of land products. This is very necessary to address the food crisis as a global challenge that requires the role of all levels of society to overcome it, including the church in it. This research was conducted using qualitative research, through a literature study approach. Then it was found that the people's food security is one of God's goals in regulating the lives of His people through the Torah law which regulates the governance of Israel's agrarian life. This is the foundation that offers a community of believers to participate in strengthening food security. A manifestation of concern that goes beyond the boundaries of faith and nationality as the church's witness in overcoming food insecurity.